The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/0104-530x4641-19
|View full text |Cite
|
Sign up to set email alerts
|

An application of Earned Value Management (EVM) with Monte Carlo simulation in engineering project management

Abstract: The fast changes in the Market make companies increasingly focus on project structures. A project differs from a routine activity because it is unique and must be managed and structured to provide expected benefits at no greater cost than anticipated. Therefore, it must be planned and controlled by identifying the deviations between the planned and the accomplished. In order to provide this monitoring, Earned Value Management (EVM) has been increasing accepted. In addition to showing indicators of progress, EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Ponz-Tienda et al 35 found that using fuzzy arithmetic on EVM provided more objective results in uncertain environments than the traditional methodology. Bonato et al 37 integrated EVM with Monte Carlo simulation to predict the final cost of three engineering projects. Batselier and Vanhoucke 38 compared the accuracy of the project time and cost forecasting using EVM and simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Ponz-Tienda et al 35 found that using fuzzy arithmetic on EVM provided more objective results in uncertain environments than the traditional methodology. Bonato et al 37 integrated EVM with Monte Carlo simulation to predict the final cost of three engineering projects. Batselier and Vanhoucke 38 compared the accuracy of the project time and cost forecasting using EVM and simulation.…”
Section: Introductionmentioning
confidence: 99%